Tsunami simulation due to seaquake at Manila Trench and Sulu Trench - Liew, M. S. (2017)
Seaquake is a phenomenon where there are water disturbance at the sea, caused by earthquake or submarine eruption. The scope of this study focuses on tsunami simulation due to Manila Trench and Sulu Trench seaquake which is prone to harm Malaysia offshore areas. Manila Trench is a highly potential earthquake source that can generate tsunami in South China Sea. Meanwhile, Sulu Trench could be a threat to east of Sabah offshore areas.